2014
DOI: 10.1186/1743-422x-11-24
|View full text |Cite
|
Sign up to set email alerts
|

Molecular epidemiology and viral load of HCV in different regions of Punjab, Pakistan

Abstract: BackgroundHepatitis C virus (HCV) is highly infectious pathogen which is responsible for causing Hepatitis around 200 million individuals worldwide. In Pakistan, 4.7% of HCV prevalence has been reported and HCV genotype 3a has been found to be the major source of infection in Pakistan but still there is lack of information on distribution of HCV genotypes and viral load in various geographical regions of Pakistan. Therefore, current study was designed to determine distribution of HCV genotypes as well viral lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
13
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 20 publications
(28 reference statements)
4
13
2
Order By: Relevance
“…This study also reported many rare genotypes like 5a, 1c, and 6a, which are uncommon and less reported. Unlike Ali et al (8) sudy findings, the findings of this study support the verdict of some previous studies that showed the presence of genotypes such as 5a, 4a, and 1c in spite of their rare status (9)(10)(11)16). These findings are in contradiction with those of some studies that have shown the partial absence of genotypes 4, 5, and 6 (8,17).…”
Section: Discussioncontrasting
confidence: 86%
See 1 more Smart Citation
“…This study also reported many rare genotypes like 5a, 1c, and 6a, which are uncommon and less reported. Unlike Ali et al (8) sudy findings, the findings of this study support the verdict of some previous studies that showed the presence of genotypes such as 5a, 4a, and 1c in spite of their rare status (9)(10)(11)16). These findings are in contradiction with those of some studies that have shown the partial absence of genotypes 4, 5, and 6 (8,17).…”
Section: Discussioncontrasting
confidence: 86%
“…It has been well-established that HCV genotype 3a is highly prevalent in Pakistani population (9,11,14). On the other hand, a single study revealed that 1a genotype has a higher frequency in Balochistan (7).…”
Section: Discussionmentioning
confidence: 99%
“…This is consistent with the results of other studies conducted in the European countries and the United States (12). The Genotype 3a was the predominant genotype in this study, which is in line with the findings of studies conducted in India, Pakistan and Nepal (13,14). However, these findings are inconsistent with the results of studies in Saudi Arabia (15), Kuwait (16), France (17), North American countries (18) and South Korea (19).…”
Section: Discussionsupporting
confidence: 86%
“…HCV infection is endemic in Pakistan (22,23,24,25); according to a recent report, the incidence of the disease has increased from 4.7% (41) to 6.8% within a couple of years (28). Unfortunately, low literacy level, inadequate public health facilities and lack of awareness are main reasons behind insufficiency of significant data about the high incidence of the disease in Pakistan.…”
Section: Hepatitis C Prevalence In Pakistanmentioning
confidence: 99%
“…Unfortunately, low literacy level, inadequate public health facilities and lack of awareness are main reasons behind insufficiency of significant data about the high incidence of the disease in Pakistan. Several studies have reported various HCV infection rates in different geographical areas and ethnic groups in Pakistan (25,26,36,64). In this review, we investigated more than twenty articles on the prevalence of HCV in the country published recently in national and international journals ( Table 1).…”
Section: Hepatitis C Prevalence In Pakistanmentioning
confidence: 99%